Evaluation the Success of ERP Implementation in Indonesia: Delonde and Mclean Model Approach - Purnomo, Indro (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
Enterprise Resource Planning (ERP) is implemented in various sectors, especially MSMEs, which are increasingly brilliant in increasing global competitiveness. In 2023, Indonesia's MSME contribution to GDP is the highest compared to other countries. ERP evaluation is important, because not all businesses achieve success. This qualitative research aims to provide an overview of the factors in evaluating the success of ERP implementation in Indonesia based on the Delone & Mclean model. These results provide an illustration, evaluation of the success of ERP implementation based on the refined Delone & McLean model can be done through the initial stage, process stage and results stage. The benefits of implementing ERP include improving individual and work group performance, market expansion, sales growth, cost and time savings.